Analysis of the Financial Performance of Indian Commercial Banks: A Comparative Study - Makkar, Anita; Singh, Shveta (Indian Journal of Finance, 2013)
Financial performance of a bank indicates the strength and weakness of that particular bank by properly establishing the association between the items of the balance sheet and profit&loss account. The present study is a comparative analysis of the financial performance of Indian commercial banks. The study considered a sample of 37 banks (22 public sector banks and 15 private sector banks) for the period from 2006-07 to 2010-11. CAMELS rating methodology was used in the study to measure the performance of the considered banks. The study found that the IDBI Bank was the best performing bank followed by Kotak Mahindra Bank and ICICI Bank. Dhanalaxmi Bank had the worst performance followed by J&K Bank and Karnataka Bank Ltd. The results of the ’t’ - test disclosed that there is a significant difference in the Capital Adequacy, Asset Quality and Earning Capacity of public and private sector banks in India, while there is no significant difference in the Management, Liquidity Position and Sensitivity to market risk of the two different banks groups. The study concluded that on an average, there is no statistically significant difference in the financial performance of the public and private sector banks in India, but still, there is a need for overall improvement in the public sector banks to make their position strong in the competitive market.